Language, Logic and Epistemology a modal-realist approach - Norris, Christopher 1947- (Palgrave Macmillan UK, 2004)
Cover -- Contents -- Acknowledgements -- Introduction -- 1 Derrida on Rousseau: Deconstruction as Philosophy of Logic -- 2 The Limits of Whose Language?: Wittgenstein on Logic, Mathematics, and Science -- 3 Modularity, Nativism, and Reference-Fixing: On Chomsky's Internalist Assumptions -- 4 The Perceiver's Share (1): Realism, Scepticism, and Response-Dependence -- 5 The Perceiver's Share (2): Deconstructive Musicology and Cognitive Science -- 6 Change, Conservation, and Crisis-Management in the Discourse of Analytic Philosophy -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- J -- K -- L -- M -- N -- P -- Q -- R -- S -- T -- V -- W -- Y.
Description based on publisher supplied metadata and other sources
Keywords: Dekonstruktion; Linguistik; Sprachphilosophie; Philosophy, Modern-20th century..; Language and languages-Philosophy..; Poststructuralism..; Postmodernism..; Logic..; Knowledge, Theory of; Electronic books